Consensual violence: sex, sports, and the politics of injury - Weinberg, Jill D. (University of California Press, 2016)
"In this novel approach to understanding consent, Jill D. Weinberg features two case studies where groups engage in seemingly violent acts: competitive mixed martial arts and sexual sadomasochism. These activities are similar in that consenting to injury is central to the activity, and participants of both activities have to engage in a form of social decriminalization, leveraging the legal authority imbued in the language of consent as a way to render their activities legally and socially tolerable. Yet, these activities are treated differently under criminal battery law. Using interviews with participants and ethnographic observation, Weinberg argues that where law authorizes a person's consent to an activity, consent is not meaningfully regulated or constructed by the participants themselves. In contrast, where law prohibits a person's consent to an activity, participants actively construct and regulate consent. This difference demonstrates that law can make consent less consensual. Synthesizing criminal law and ethnography, Consensual Violence is a fascinating account of how consent gets created and carried out among participants and lays the groundwork for a sociology of consent and a more sociological understanding of processes of decriminalization."--Provided by publisher